LEO satellite formation for SSP : energy and doppler analysis - Goh, Shu Ting (2015)
The space-based solar power (SBSP) concept was introduced during the 1970s. However, the technological challenges during that period stalled its development. Decaying natural energy resources, global warming, and geopolitical pressures have encouraged many countries and researchers to seek new reliable energy sources, such as SBSP. A solar power technology that comprises low Earth orbit (LEO) spacecraft formation has been proposed in the literature. All spacecraft in the LEO formation harvest solar energy and transmit the power to a leader spacecraft or the ground station simultaneously. In the proposed LEO technique, the high and varying relative speed within the spacecraft formation, and also within the spacecraft and the Earth, causes a nonhomogeneous Doppler spread during solar power transmission. This Doppler spread reduces SBSP power transmission efficiency. In this paper, first, the transmission link budget from LEO and geostationary orbits to the Earth are compared, and the harvested energy by the ground station on the Earth is investigated. This motivates low or mid Earth orbit satellite usage for SBSP. Next, considering different spacecraft configurations, the impact of the distance between each spacecraft and the ground station, and the distance between each spacecraft and the leader spacecraft on the variation of the Doppler frequency spread is investigated. In addition, the impact of the position of the leader spacecraft with respect to other spacecraft in the formation is studied. The results confirm that higher altitude or smaller formation size leads to lower Doppler frequency spread in the transmission between each spacecraft to the ground station (or leader spacecraft). Finally, several possible techniques to improve the wireless power transmission efficiency due to the Doppler effect are discussed and compared.